2012
DOI: 10.1002/prot.24152
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure and siRNA‐mediated knockdown analysis of the mitochondrial disease‐related protein C12orf65

Abstract: Loss of function of the c12orf65 gene causes a mitochondrial translation defect, leading to encephalomyopathy. The C12orf65 protein is thought to play a role similar to that of ICT1 in rescuing stalled mitoribosomes during translation. Both proteins belong to a family of Class I peptide release factors (RFs), all characterized by the presence of a GGQ motif. Here, we determined the solution structure of the GGQ-containing domain (GGQ domain) of C12orf65 from mouse by NMR spectroscopy, and examined the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…Kogure et al (2) found that knockdown of the C12orf65 protein in cell culture assays resulted in an increase in reactive oxygen species and apoptosis. Mitochondrial dysfunction was demonstrated by impaired cytochrome c oxidase activity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Kogure et al (2) found that knockdown of the C12orf65 protein in cell culture assays resulted in an increase in reactive oxygen species and apoptosis. Mitochondrial dysfunction was demonstrated by impaired cytochrome c oxidase activity.…”
Section: Discussionmentioning
confidence: 98%
“…The C12orf65 gene encodes a mitochondrial matrix protein that is critical for the release of newly synthesized proteins from mitochondrial ribosomes. Loss-of-function mutations impair the translation of mitochondrial proteins, with a resultant decrease in the protein complexes necessary for effective oxidative phosphorylation (1,2). The COXPD7 phenotype has been described in 2 distinct pedigrees by Antonicka et al (1).…”
mentioning
confidence: 97%
“…6 The entire group of the organellar release-factor family is characterized by the presence of a conserved peptidyl-hydrolase domain containing the universally conserved Gly-Gly-Gln (GGQ) motif, 7 which interacts with the large ribosomal subunit to release the polypeptide chain from the P-site bound peptidyl-tRNA. This GGQ-containing domain stretching from amino acid 57 to 121 in the human 166-residue full-length protein 8 is not affected by the mutations that lead to a relatively mild phenotype. However, both in family B and in the previously described patients with the severe phenotype 2 the mutation interrupts this highly conserved domain C12orf65 and ICT1, in contrast to other class I release factors, share C-terminal region comprising 20 basic residues.…”
Section: Discussionmentioning
confidence: 99%
“…However, both in family B and in the previously described patients with the severe phenotype 2 the mutation interrupts this highly conserved domain C12orf65 and ICT1, in contrast to other class I release factors, share C-terminal region comprising 20 basic residues. 8 Gagnon et al 9 showed that in the bacterial ICT1 homolog, YaeJ, the C-terminal tail functions as a sensor to discriminate between stalled and actively translating ribosomes. The mutations leading to a mild phenotype are expected to cause, in addition to a shortened C terminus, a less basiccharged tail, which may reduce the effectiveness of the interaction with the phosphate backbone of the ribosomal RNA that forms the walls of the ribosomal channel.…”
Section: Discussionmentioning
confidence: 99%
“…These insertions consist of three amino acids (Gly-Leu-Ser) in the stop codon recognition loop and two residues (Arg-Thr) in the short loop preceding the a5 helix. The other two homologues of the bacterial release factors (RFs), ICT1 and C12orf65, are both mitochondrial proteins with critical functions for cell viability and have been proposed to be involved in rescuing stalled ribosomes 9,15,16 . ICT1 has further been shown to be an integral part of the mitoribosome 9 .…”
mentioning
confidence: 99%